Analysis of operator’s flow middle platform in 5G+native system - Yingqi WEI; Weiping LIN; Ying LI; Hua TAN (Dianxin kexue)
Based on the 5G mobile network,the traffic middle station was proposed,and the structure of the traffic middle station was introduced in detail.Flow middle platform highly abstracts the 5G connection management and flow delicacy control functions,simplify the operator’s traditional complicated IT interfaces,combines with data intelligent analysis.It helps massive industrial endpoints to access the 5G networks,build data connections to applications.It supports radio connection functions out of the box,frees the 5G industry internet application developers from intricacy radio connection development.